Left Atrial Appendage Closure Guided by 3D Printed Cardiac Reconstruction: Emerging Directions and Future Trends. (5th April 2016) - PELLEGRINO, PIER LUIGI; FASSINI, GAETANO; DI BIASE, MATTEO; TONDO, CLAUDIO
Emerging Directions and Future Trends: Introduction: Percutaneous left atrial appendage (LAA) occlusion has emerged as an alternative therapeutic approach to medical therapy for stroke prevention in patients with atrial fibrillation. 3D printing is a novel technology able to create a patient specific model of any given anatomical portion of the heart. Results: Herein we report the first 2 cases of LAA occlusion procedure with 2 different systems, the Wave Crest device (Coherex Medical, Inc., USA) and the Amplatzer Amulet device (St. Jude Medical, St. Paul, MN, USA), in which a 3D printed LAA model (Care Tronik, Prato, Italy) was used in a rehearse phase. Both patients had history of paroxysmal AF and previous transient ischemic attack (TIA) occurred during oral anticoagulation with correct INR. In the first patient the occlusive device was positioned within the LAA after a rehearse occlusion using the 3D printed LAA plus a 27 mm Coherex Wavecrest device, demonstrating a good compression and sealing, particularly considering a proximal lobe of the appendage. In the second patient an attempt with the 27 mm Amulet device delivered within the 3D printed LAA, based on angiography and transesophageal echocardiographic (TEE), revealed insufficient covering of the proximal part of LAA vestibule; the device was released only after a second test with the 31 mm Amulet demonstrating a good sealing. Conclusion: These 2 cases demonstrated that 3D model could help in finding the correct position within LAA, sizing the device and guiding the choice of the closure device despite the measurements provided by angiography and TEE.